2005
DOI: 10.1210/jc.2004-0663
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Gap Junctional Intercellular Communication and Connexin43 Expression by Retinoic Acid in Human Endometrial Stromal Cells

Abstract: Phosphorylation of Cx43 is inversely related to GJIC in endometrial stromal cells. Retinoids increase GJIC in endomentrial stromal cells through upregulation of Cx43 expression while inducing a decrease in the phosphorylated species of the protein. The data suggest a novel mechanism by which retinoids can influence endometrial cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…Levels of gap junctional intercellular communication (GJIC) in control and treated cells in culture were determined by SL/DT (Scrape Loading/Dye Transfer) technique using a fluorescent dye, Lucifer Yellow (LY) (Invitrogen, Eugene, OR) [12,13]. hSV SMCs were washed thoroughly with PBS in which Ca 2+ was omitted to prevent uncoupling of the cells.…”
Section: Scrape Loading/dye Transfermentioning
confidence: 99%
“…Levels of gap junctional intercellular communication (GJIC) in control and treated cells in culture were determined by SL/DT (Scrape Loading/Dye Transfer) technique using a fluorescent dye, Lucifer Yellow (LY) (Invitrogen, Eugene, OR) [12,13]. hSV SMCs were washed thoroughly with PBS in which Ca 2+ was omitted to prevent uncoupling of the cells.…”
Section: Scrape Loading/dye Transfermentioning
confidence: 99%
“…RA and other retinoids enhance GJIC and CX43 expression levels in numerous cell types, certain human cancer cell types, mouse fibroblasts and rat liver cells, through transcriptional and translational mechanisms (Stahl & Sies 1998, Carystinos et al 2001. When treated with RA, CX43 expression in human endometrial stromal cells shows a dose-dependent increase at the mRNA and protein levels (Tanmahasamut & Sidell 2005) (Table 2). Concomitant with the increase in CX43 expression, stromal cells treated with RA exhibit a 2.5-fold enhancement in their GJIC as assessed by dye transfer experiments (Tanmahasamut & Sidell 2005).…”
Section: Gap Junction Intercellular Communicationsmentioning
confidence: 99%
“…The expression of these same genes can be modulated by ovarian steroid hormones (i.e., estradiol and progesterone) treatment (Vermot et al 2000, Li & Ong 2003, Rühl et al 2006, Fritzsche et al 2007). The retinoid pathway is known to play vital roles in endometrial development and differentiation (Tanmahasamut & Sidell 2005, Wu et al 2013, Nakajima et al 2016, as well as endometrial neovascularization (Sidell et al 2010) and blastocyst implantation (Han et al 2010, Ma et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the role of HUVEC connexins on monocyte-endothelial adhesion, HUVEC were treated with oleamide, which rapidly inhibited Cx channels, including Cx43 (14), or with retinoic acid, which our previous study demonstrated increases the expression of Cx43 in these cells (15). The effects of oleamide and retinoic acid treatment on U937-HUVEC adhesion, Cx43 expression and ATP release were determined.…”
Section: Effects Of Oleamide and Retinoic Acid Treatment On The Exprementioning
confidence: 99%